The strength of surgical repairs of the rotator cuff. A biomechanical study on cadavers. - Sward,L; Hughes,JS; Amis,A; Wallace,WA (J Bone Joint Surg Br, 1992)
Using 26 cadaver shoulders, we produced a standard defect in the supraspinatus tendon and performed one of three types of repair. Their strength was found by testing in tension the force required to produce a gap of 3 mm, then 6 mm, and finally total disruption of the repair. The use of a polyethylene patch to spread the forces over the lateral bone surface and of extra sutures to grasp the tendon end raised by 2.6 times the load at which a 3 mm gap in the repair occurred and by 1.7 times the load to failure.